Thionation of the 2‐λ5‐Phosphaquinolin‐2‐one Scaffold with Lawesson's Reagent. Issue 3 (14th December 2020) - Bard, Jeremy P.; McNeill, J. Nolan; Warren, Gabrielle I.; Zakharov, Lev N.; Johnson, Darren W.; Haley, Michael M.
Abstract: Lawesson's reagent is one of the most common thionating reagents that has found use for several decades on a variety of carbonyl systems. Herein, we report the transformation of the 2‐λ 5 ‐phosphaquinolin‐2‐one structure to its respective 2‐λ 5 ‐phosphaquinolin‐2‐thione derivative. Solution‐state characterization of both P−OPh and P−Ph thio analogues, as well as solid‐state structures for the latter system, are reported. Abstract :